Novel ZnO-Based Nanostructures Synthesis, Characterization and Applications - Leprince-Wang, Yamin; Jing, Guangyin; El Zein, Basma (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Zinc oxide (ZnO) nanostructure, one of most famous nanomaterials in past decades, provides extensive and adaptive applications to wide communities include material, physics, daily-use chemical industry and medical societies. Controlled synthesis, advancing characterization tools, and endless healthcare from materials, drive rapid evolution of understanding and engineering on ZnO nanomaterials. Here, in this reprint, novel research articles and mini reviews are included with the focus on the novel synthesis, applications on the air and liquid purifications by using the photocatalytic merits of ZnO. Additionally, antibacterial performance from the ZnO nanostructures were demonstrated by these original contributions, which directs the new possibility from ZnO towards medical usage.